Functional biodiversity loss along natural CO2 gradients - Nuria Teixidó (Nature Portfolio, 2018)
Locations in the ocean where CO2 naturally seeps from the seafloor can be used to infer potential responses to ocean acidification. Here the authors explore the functional composition of benthic communities along a natural CO2 gradient, showing a loss of functional diversity at high-CO2 sites.